Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Elevated plasma phage load as a marker for intestinal permeability in leukemic patients - Xue-rui Yin; Ping Liu; Xi Xu; Ying Xia; Kai-zhao Huang; Qiong-dan Wang; Mei-mei Lai; Qi-gui Yu; Xiao-qun Zheng (Medical Microbiology and Immunology, 2020)

Rho GTPases in cancer radiotherapy and metastasis - Rui-Jie Zeng; Chun-Wen Zheng; Wan-Xian Chen; Li-Yan Xu; En-Min Li (Cancer and Metastasis Reviews, 2020)

MHC-DRB1 exon 2 polymorphism and its association with mycoplasma ovipneumonia resistance or susceptibility genotypes in sheep - Kaisheng Wang; Xianxia Liu; Qiongqiong Li; Kexing Wan; Rui Gao; Guohua Han; Chaochen Li; Mengsi Xu; Bin Jia; Xiaoyun Shen (Journal of Genetics, 2020)

Correction to: Diffuse leptomeningeal glioneuronal tumor in a Chinese adult: a novel case report and review of literature - Honghao Xu; Fangqing Chen; Haitao Zhu; Lei Luo; Rui Zhang (Acta Neurologica Belgica, 2020)

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Utilizing borehole electrical image and conventional logs to characterize petrology of mixed volcanic and sedimentary rocks in Jiamuhe Formation at JL2 Wellfield, Zhongguai Uplift, Junggar Basin, NW China - Rui Yuan; Lei Zhang; Qinghai Xu; Youlun Feng; Zhiyuan An; Jun Wu; Kang Zhao; Shuai Liu; Peng Huang (Arabian Journal of Geosciences, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

The Protective Effect of Safinamide in Ischemic Stroke Mice and a Brain Endothelial Cell Line - Tingting Xu; Rui Sun; Guoshi Wei; Shanshan Kong (Neurotoxicity Research, 2020)

Evaluating Spatial Heterogeneity of Land Surface Hydrothermal Conditions in the Heihe River Basin - Yuan Zhang; Shaomin Liu; Xiao Hu; Jianghao Wang; Xiang Li; Ziwei Xu; Yanfei Ma; Rui Liu; Tongren Xu; Xiaofan Yang (Chinese Geographical Science, 2020)

Complete genome sequence of a novel mycovirus isolated from the phytopathogenic fungus Corynespora cassiicola in China - Yanfen Wang; Hang Zhao; Caiying Xue; Chao Xu; Yuehua Geng; Rui Zang; Yuxia Guo; Haiyan Wu; Meng Zhang (Archives of Virology, 2020)

BDNF improves axon transportation and rescues visual function in a rodent model of acute elevation of intraocular pressure - Rui Du; Xu Wang; Shigang He (Science China Life Sciences, 2020)

Mapping spatio-temporal dynamics of main water parameters and understanding their relationships with driving factors using GF-1 images in a clear reservoir - Shuai Zeng; Yunmei Li; Heng Lyu; Jiafeng Xu; Xianzhang Dong; Rui Wang; Ziqian Yang; Jianchao Li (Environmental Science and Pollution Research, 2020)

Alleviation of Cd phytotoxicity and enhancement of rape seedling growth by plant growth–promoting bacterium Enterobacter sp. Zm-123 - Meng Zhang; Zonghui Jin; Xu Zhang; Guoliang Wang; Rui Li; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

An improved FAHP based methodology for groundwater potential zones in Longchuan River basin, Yunnan Province, China - Dayou Luo; Xingping Wen; Haonan Zhang; Junlong Xu; Rui Zhang (Earth Science Informatics, 2020)

A State-Dependent Constitutive Model for Gas Hydrate-Bearing Sediments Considering Cementing Effect - Qingmeng Yuan; Liang Kong; Rui Xu; Yapeng Zhao (Journal of Marine Science and Engineering, 2020)
This paper presents a state-dependent constitutive model for gas hydrate-bearing sediments (GHBS), considering the cementing effect for simulating the stress–strain behavior of GHBS. In this work, to consider the influence of hydrate on matrix samples in theory, some representative GHBS laboratory tests were analyzed, and it was found that GHBS has obvious state-related characteristics. At the same time, it was found that GHBS has high bonding strength. In order to describe these characteristics of GHBS, the cementation strength related to hydrate saturation is introduced in the framework of a sand state correlation model. In addition, in order to accurately reflect the influence of cementation on the hardening law of GHBS, the degradation rate of cementation strength is introduced, and the mixed hardening theory is adopted to establish the constitutive model. The model presented in this paper reproduces the experimental results of Masui et al. and Miyazaki et al., and the prediction performance of the model is satisfactory, which proves the rationality of this work.

Molecular Characterization and Promoter Analysis of Novel Sugar Transporter Gene ScERD6 in Sugarcane - Xiao-Rong Miao; Xu-Peng Zeng; Jun-Qi Niu; Aamir Mahmood; Li-Tao Yang; Bao-Qing Zhang; Yang-Rui Li (Sugar Tech, 2020)

Effects of crop straw biochars on aluminum species in soil solution as related with the growth and yield of canola (Brassica napus L.) in an acidic Ultisol under field condition - Wen-rui Zhao; Jiu-yu Li; Kai-ying Deng; Ren-yong Shi; Jun Jiang; Zhi-neng Hong; Wei Qian; Xian He; Ren-kou Xu (Environmental Science and Pollution Research, 2020)

The impact of prenatal exposure to PM2.5 on childhood asthma and wheezing: a meta-analysis of observational studies - Wu Yan; Xu Wang; Tianyu Dong; Mengqi Sun; Mingzhi Zhang; Kacey Fang; Yi Chen; Rui Chen; Zhiwei Sun; Yankai Xia (Environmental Science and Pollution Research, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Genetic variants in Ras/Raf/MEK/ERK pathway are associated with gastric cancer risk in Chinese Han population - Xiaowei Wang; Xu Wu; Junyi Xin; Shuwei Li; Rui Zheng; Dan Guan; Weida Gong; Qinghong Zhao; Meilin Wang; Haiyan Chu; Mulong Du; Guoquan Tao; et al. (Archives of Toxicology, 2020)

Overexpression of Purinergic P2X4 Receptors in Hippocampus Rescues Memory Impairment in Rats with Type 2 Diabetes - Ping-An Zhang; Qian Sun; Yong-Chang Li; Rui-Xia Weng; Rui Wu; Hong-Hong Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Purinergic receptors have been reported to be involved in brain disorders. In this study, we explored their roles and mechanisms underlying the memory impairment in rats with type 2 diabetes mellitus (T2DM). T2DM rats exhibited a worse performance in the T-maze and Morris water maze (MWM) than controls. Microglia positive for P2X purinoceptor 4 (P2X4R) in the hippocampus were reduced and activated microglia were increased in T2DM rats. Long Amplicon PCR (LA-PCR) showed that DNA amplification of the p2x4r gene in the hippocampus was lower in T2DM rats. Minocycline significantly reduced the number of activated microglia and the mean distance traveled by T2DM rats in the MWM. Most importantly, P2X4R overexpression suppressed the activated microglia and rescued the memory impairment of T2DM rats. Overall, T2DM led to excessive activation of microglia in the hippocampus, partly through the DNA damage-mediated downregulation of P2X4Rs, thus contributing to memory impairment.

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Effects of different NO3−:NH4+ ratios on the photosynthesis and ultrastructure of lettuce seedlings - Xu Zhu; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2020)

In vitro and in vivo evaluation of the antifungal activity of fluoxetine combined with antifungals against Candida albicans biofilms and oral candidiasis - Liuliu Jiang; Linxia Zheng; K airui Sun; Peng Zhou; Rui Xu; Jingyi Gu; Xin Wei (Biofouling, 2020)

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Two-Dimensional Discrepancies in Fracture Geometric Factors and Connectivity Between Field-Collected and Stochastically Modeled DFNs: A Case Study of Sluice Foundation Rock Mass in Datengxia, China - Wen Zhang; Rui Fu; Chun Tan; Zhifa Ma; Ying Zhang; Shengyuan Song; Peihua Xu; Shuonan Wang; Yunpeng Zhao (Rock Mechanics and Rock Engineering, 2020)

PDB-1 from Potentilla discolor Bunge suppresses lung cancer cell migration and invasion via FAK/Src and MAPK signaling pathways - Na-na Meng; Rui-rui Zhang; Chao Liu; Qing Wang; Xin-kun Wang; Xu Guo; Ping-ping Wang; Jin-yue Sun (Medicinal Chemistry Research, 2020)

Spent mushroom substrate combined with alkaline amendment passivates cadmium and improves soil property - Zonghui Jin; Meng Zhang; Rui Li; Xu Zhang; Guoliang Wang; Xuesheng Liu; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Long-term fertilization and intensive cropping enhance carbon and nitrogen accumulated in soil clay-sized particles of red soil in South China - Hu Xu; Kailou Liu; Wenju Zhang; Yichao Rui; Jingye Zhang; Lei Wu; Gilles Colinet; Qinghai Huang; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2020)

Solar UV radiation exacerbates photoinhibition of a diatom by antifouling agents Irgarol 1051 and diuron - Rui Hou; Yaping Wu; Juntian Xu; Kunshan Gao (Journal of Applied Phycology, 2020)

Appropriate Dynamically-Reinforced Supporting Time Determination in Relation to the Time Effect of Stress Field Evolution: A Case Study on the Deep Soft-Rock Roadway in China - Li Cong; Ying-ming Li; Xiang-rui Meng; Chun-liang Dong; Guang-ming Zhao; Rui Peng; Ji-cheng Xu (Geotechnical and Geological Engineering, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Sulfur content in coal formed during different geologic periods in the Guangxi Province and the relationship with the depositional environment - Bohui Xu; Yuxin Song; Yuan Tian; Rui Yang; Fei Xu; Shuli Ding; Pengfei Sun (Arabian Journal of Geosciences, 2020)

Diffuse leptomeningeal glioneuronal tumor in a Chinese adult: a novel case report and review of literature - Honghao Xu; Fangqing Chen; Haitao Zhu; Lei Luo; Rui Zhang (Acta Neurologica Belgica, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

Decreasing intraocular pressure significantly improves retinal vessel density, cytoarchitecture and visual function in rodent oxygen induced retinopathy - Rui Du; Xu Wang; Ke Shen; Shigang He (Science China Life Sciences, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Risk factors and clinical characteristics of tacrolimus-induced acute nephrotoxicity in children with nephrotic syndrome: a retrospective case-control study - Ping Gao; Xin-Lei Guan; Rui Huang; Xiao-Fang Shang-guan; Jiang-Wei Luan; Mao-Chang Liu; Hua Xu; Xiao-Wen Wang (European Journal of Clinical Pharmacology, 2020)

Forest gaps retard carbon and nutrient release from twig litter in alpine forest ecosystems - Bo Tan; Jian Zhang; Wanqin Yang; Rui Yin; Zhenfeng Xu; Yang Liu; Li Zhang; Han Li; Chengming You (European Journal of Forest Research, 2020)

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

LncRNA NBR2 suppresses migration and invasion of colorectal cancer cells by downregulating miRNA-21 - Jinghui Bai; Jian Xu; Jian Zhao; Rui Zhang (Human Cell, 2020)

Strength Parameters of Rock Considering Area and Stress Correction During Shearing - Hang Lin; Yushan Hua; Rui Yong; Daxing Lei; Wanzhong Xu; Shigui Du (Geotechnical and Geological Engineering, 2020)

Uptake and accumulation of pentachloronitrobenzene in pak choi and the human health risk - Ming Li; Guanghui Xu; Rui Yu; Yang Wang; Yong Yu (Environmental Geochemistry and Health, 2020)

Genetic variants in circTUBB interacting with smoking can enhance colorectal cancer risk - Ke Zhang; Shuwei Li; Dongying Gu; Kaili Xu; Rui Zheng; Junyi Xin; Yixuan Meng; Shuai Ben; Haiyan Chu; Zhengdong Zhang; Yongqian Shu; Mulong Du; et al. (Archives of Toxicology, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)